Pemberdayaan Taman Sekolah melalui Akuaponik untuk Menumbuhkan Kemandirian dan Kerjasama Siswa di SD Negeri Jatimulyo 03 Malang - Yuniawatika, Yuniawatika; Astuti, Adinda Ajeng Rindu; Sidiq, Ahmad; Wahyuni, Alfika; Prameswari, Caket; Heriyanti, Candra Ika; Sukarno, Damai Nur; Diana, Dela; Yulianti, Dita (Universitas Nusantara PGRI Kediri, 2025)
The suboptimal use of school gardens as a contextual learning tool is a major issue at SDN Jatimulyo 03 Malang. This community service program aims to empower the school garden through the implementation of an aquaponics system to foster independence and cooperation in students. The program was implemented by students of the Teacher Professional Education (PPG) program at the State University of Malang using a project-based approach and participatory methods. The project included initial observation, planning, outreach and training, implementation of the aquaponics system with kale and catfish, and evaluation and reflection. The results showed significant improvements in students' independence, cooperation, and environmental awareness. Students were actively involved in system maintenance, demonstrated initiative in dividing tasks, and developed a sense of responsibility and teamwork skills. Furthermore, teachers assessed the aquaponics system as a potential learning medium across subjects. Key challenges related to program sustainability were addressed through the development of maintenance modules, a scheduled duty system, and parental involvement. This program has proven effective in integrating character education with hands-on practice and has the potential to be replicated in other schools as an alternative to 21st-century contextual learning.